(untitled) (Revista Inclusiones, 2021)
The search for the national identity is a central theme in Julian Barnes’s England, England (1999). The article studies various aspects of the physical representation of the idea in the novel. On the one hand, the landscape in the novel is tightly connected with the historical and pseudo-historical meanings which make it an essential part of Barnes’s model of the national identity. On the other hand, the novel recreates the process of physical reshaping of the national landscape as a metaphor for reshaping the nation. The article proves that the three landscapes successively emerging in the three parts of the novel are endowed with various degrees of symbolic meaning. The first part of the novel presents the landscape of the childhood memories blended with the character’s emotional reminiscences. The second part focuses on role the simulacrum landscape plays in the myth creation as the quintessence of Englishness is materialised in the replicas of historic and cultural sites in the theme park. In the third par, Anglia’s landscape is shown as devoid of any historical meaning for the inhabitants of the island.